2018
DOI: 10.1016/j.bbrc.2018.02.170
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein A2 isoforms in autoimmune pancreatitis

Abstract: Recently, apolipoprotein A2 (apoA2) isoforms have been reported as candidate serum/plasma biomarkers of pancreatic cancer. However, the distribution of apoA2 isoforms in patients with autoimmune pancreatitis (AIP) has not been investigated yet. In this study, we evaluated the distribution of serum apoA2 isoforms; i.e., homodimer apoA2-ATQ/ATQ, heterodimer apoA2-ATQ/AT, and homodimer apoA2-AT/AT, in AIP patients and healthy volunteers (HV) using enzyme-linked immunosorbent assays, and the clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We have previously reported that specific abnormal processing patterns of the amino acids at the C-terminal ends of apoA2 homodimers are observed in pancreatic diseases. These processing patterns might be useful for distinguishing PC from CP or AIP, and might also be key to elucidating why the plasma apoA2-ATQ/AT level is useful as a biomarker of PC [ 26 ]. Hayasaki et al [ 27 ] recently reported that pancreatic atrophy and insufficient secretion of circulating pancreatic enzymes might influence apoA2-ATQ levels, and suggested that apoA2-ATQ levels could offer a useful biomarker for assessing pancreatic exocrine disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that specific abnormal processing patterns of the amino acids at the C-terminal ends of apoA2 homodimers are observed in pancreatic diseases. These processing patterns might be useful for distinguishing PC from CP or AIP, and might also be key to elucidating why the plasma apoA2-ATQ/AT level is useful as a biomarker of PC [ 26 ]. Hayasaki et al [ 27 ] recently reported that pancreatic atrophy and insufficient secretion of circulating pancreatic enzymes might influence apoA2-ATQ levels, and suggested that apoA2-ATQ levels could offer a useful biomarker for assessing pancreatic exocrine disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest apoA2 isoforms as potential biomarkers for filtering the general population for individuals at higher risk of PDAC. Although the mechanisms underlying these findings are still unknown, we have previously reported that specific abnormal processing patterns of amino acid in the C-terminal ends of apoA2 homodimer were observed in PDAC or autoimmune pancreatitis (AIP) [27,28]. Hayasaki et al recently reported that apoA2-ATQ levels seem to reflect pancreatic atrophy and insufficient secretion of circulating pancreatic enzymes, and could provide a biomarker to assess pancreatic exocrine disorder [29].…”
Section: Blood-based Biomarkers For Early Detection Of Pdacmentioning
confidence: 99%
“…It seems that the unique alteration of processing patterns of apoA2-i in pancreatic disorders is associated with the exocrine function of the pancreas. In fact, Kobayashi et al recently reported that a significant increase of apoA2-ATQ/ATQ as a heavy homodimer was observed in autoimmune pancreatitis (AIP), in comparison with apoA2-AT/AT, and, in particular, many cases with extremely decreased apoA2-AT/AT were observed in AIP [ 17 ]. Thus, a hypo-processing pattern of apoA2-i is a unique finding in AIP, and a significant decrease of apoA2-AT/AT may be associated with the reduction of the exocrine function of the pancreas that occurs in AIP.…”
Section: Aberrant Alteration Of Unique Processing Of C-terminal Amino...mentioning
confidence: 99%